What is the Element of the Smart Village Model?: Domains, aspects and indicators - Aziiza, Arizia Aulia; Sulistiyani, Endang; Fitri, Anindo Saka (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
The idea of "smart villages" doesn't mean that all villages have the same solution. The goal of this study has two-step plan for a "smart village". First is making a model of a smart village based on a review of the literature. Second, verification of the proposed model by interviewing the respondent. In accordance with the proposed model, exploration is conducted at the stage of verification using open-ended questions. As a result of verification, each indicator receives an additional form of explanatory indicators that are matched to the case study's conditions. This is qualitative research with multiple units of analysis based on a single case study. The case study is Banyuwangi Regency. The units of analysis are Kampung Anyar Village, Kaligondo Village, Wringinrejo Village, Tambong Village, and the Department of Community and Village Empowerment. This villages that have won the smart village competition from 2016 to 2019 in Banyuwangi. The result model consists of 6 domains, 17 aspects, and 55 indicators. The domain is governance, basic village services, village resources, the economy, infrastrucutre, and tourism. All domains, aspects, and indicators can be implemented in smart village development by making technology an enabler, and there are sustainable elements.